2022
DOI: 10.1111/jonm.13782
|View full text |Cite
|
Sign up to set email alerts
|

Career identity and career success among Chinese male nurses: The mediating role of work engagement

Abstract: Aim This study aimed to investigate the effect of career identity on career success among Chinese male nurses and to examine the mediating role of work engagement in this relationship. Background Recently, with the development of the nursing career, male nurses take up a higher share and play a more important role in the nursing team. With its own particularity and advantages, this group's stability closely relates to the future of the nursing team. Therefore, promoting the career success of the male nurses is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…These "involuntary" nursing students are involved in the nursing sector because they are forced to transfer to the nursing major due to poor grades on the college entrance exam or they choose the nursing major against their will due to pressure from their relatives and friends. Such students lack an in-depth understanding of the nursing sector and lack excitement for the nursing industry, which diminishes to some extent the perception of nursing students' decent work [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…These "involuntary" nursing students are involved in the nursing sector because they are forced to transfer to the nursing major due to poor grades on the college entrance exam or they choose the nursing major against their will due to pressure from their relatives and friends. Such students lack an in-depth understanding of the nursing sector and lack excitement for the nursing industry, which diminishes to some extent the perception of nursing students' decent work [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous research has reported that a high level of career identity leads to career success and that nurses’ work engagement is a mediating variable 25 . In other words, enhancing professional identity increases work engagement, leading to career success.…”
Section: Discussionmentioning
confidence: 99%
“…Resilience serves as a work resource that enables nurses to actively confront and effectively manage the stresses and obstacles at work, spark workplace excitement, and enhance career identity. According to research, career identity and work engagement are close relationships ( Wu et al, 2022 ). People with a strong career identity tend to devote more time and energy to their jobs and find it easier to get positive feedback from employers ( Sun et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%